Membaca Fenomena Shalat Sebagai Sebuah Tanda - Aris Fauzan (Jurnal Dakwah dan Komunikasi, 2017)
This paper attempts to read the phenomenon of prayer as a sign by placing prayer as a result of social construction. This is triggered by the emergence of the assumption that some people who try to simplify prayers by replacing them with other activities such as recall (in any condition) and do good. Furthermore the author asks the question as follows: What is the meaning of prayer in the religious tradition? How to understand prayer in the reading of dialectics-normative and social sign? To answer the question, the writer uses normative dialectic reading pattern and semiotic approach (signology). The results of the study of the authors do is: first, physically lahiriyah, prayer directs the perpetrators into a knot (an important point) on the universal website that unites between Muslims wherever they are and from whatever madhhab he embraces. Second, spiritually spiritual, prayer builds personal reinforcement that is in the primordial realiatation with the continuous reality of sharia. This continuity not only connects to the spiritual experience of fellow Muslims around the world, but also connects the experience of a Muslim with the spirituality of Abraham and Muhammad. Third, that shalat and shahadah are two things inseparable spiritually and physically, both in essence and shari'a